Incidence and Persistence of Viral Shedding in COVID-19 Post-acute Patients With Negativized Pharyngeal Swab: A Systematic Review - Morone, Giovanni; Palomba, Angela; Iosa, Marco; Caporaso, Teodorico; De Angelis, Domenico; Venturiero, Vincenzo; Savo, Anna; Coiro, Paola; Carbone, Dario; Gimigliano, Francesca; Iolascon, Giovanni; Paolucci, Stefano (Frontiers in Medicine, 2020)
After SARS-CoV2 spreading throughout the world, factors influencing viral diffusion are obtaining great attention. Human-to-human transmission mainly occurs through droplets, but viral RNA clearance in different biological fluids in COVID-19 patients remains unclear. The aim of the present work was to correlate the presence and the relevant temporal patterns of SARS-CoV2 viral RNA in biological specimens (stools, urine, blood, tears) of the transmission with clinical/epidemiological features in patients with COVID-19. We focused on the time window between the positivity of RT-PCR tests from different specimens. Mantel-Cox Log Rank test was used to verify the differences in terms of viral shedding duration, while Mann-Whitney u-test was used for subgroup analysis. We found 141 studies, 55 of which (1348 patients) were included for epidemiological analysis and 37 of which (364 patients) for statistical analysis. The most frequently assessed samples (after respiratory tract swabs) were stools, with a positivity rate of 48.8%. To overcome the possible heterogeneity within and between studies, the analyses were performed on single-patient data. The most frequently used specimens other than respiratory tract swabs were stools (or anal/rectal swabs), with a positivity rate of 48.8%, followed by urine samples, with a positivity rate of 16.4%, while blood samples showed a positivity rate of 17.5%. We found that fecal positivity duration (median 14 days) was significantly (p<0.001) longer than respiratory tract one (median 19 days). Few data are available about the other specimens. In conclusion, medical and social communities have to pay close attention on negativized COVID-19 subjects, because they could have longer alternative viral shedding.